German phonology an optimality-theoretic approach - Féry, Caroline 1953- (Cambridge University Press, 2025)
Drawing on an optimality-theoretic framework, this book provides a comprehensive overview of the phonology of German, with its idiosyncratic array of sound patterns. It starts with the consonants and vowels and the distinctive features they consist of, moving on to account for allophonic changes in detail, as well as syllables and their weight units. Phonological processes are then explored in depth, with chapter-length explorations of feet, prosodic words, prosodic phrases, and intonation phrases, showing that the prosodic hierarchy provides the domains of most phonological processes. It also includes discussions of the interfaces of morphology and syntax with phonology, as well as prosodic phrasing and intonation. The constraint-based approach allows a new holistic perspective, simultaneously encompassing all aspects of German phonology. Wide-ranging yet accessible, it is essential reading for advanced students of both linguistics and German, as well as individual scholars seeking a one-stop resource on the topic